2010
DOI: 10.1111/j.1750-3841.2010.01840.x
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Oryzacystatin for Regulating the Ripening of Squid Shiokara, a Traditional Japanese Salted and Fermented Seafood

Abstract: Shiokara is a fermented seafood composed of sliced squid mantle muscle ripened with fresh squid liver. Preliminary sensory evaluation by using the ranking test revealed that the hardness of squid muscle in shiokara was reduced within 7 d of ripening. During the process of ripening, muscle proteins were digested by proteinases present in squid liver. The degradation of paramyosin and myosin heavy chain was observed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The hardness of squid mantle muscle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…1, proteins extracted from S. japonicus muscle tissues (sjMTs) were primarily MHCs, Pm, and Ac having a molecular mass of approximately 200, 98, and 42 kDa, respectively, which is in agreement with our previous study (8). Paramyosin is abundant in most invertebrate muscles, including those from Mollusca and Arthropoda, such as squid (11), octopus (23), and crayfish (12) matching the molecular mass of 97-110 kDa (24).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…1, proteins extracted from S. japonicus muscle tissues (sjMTs) were primarily MHCs, Pm, and Ac having a molecular mass of approximately 200, 98, and 42 kDa, respectively, which is in agreement with our previous study (8). Paramyosin is abundant in most invertebrate muscles, including those from Mollusca and Arthropoda, such as squid (11), octopus (23), and crayfish (12) matching the molecular mass of 97-110 kDa (24).…”
Section: Resultssupporting
confidence: 90%
“…Proteins from muscle tissues of sea cucumber are mainly myosin heavy chains (MHCs), paramyosin (Pm), and actin (Ac) (8). MHCs and Ac are primary myofibrillar proteins in muscle tissues of aquatic animals, and Pm is abundant in most invertebrate muscles (9)(10)(11)(12). Our previous study reported that the noncollagenous proteins in S. japonicus body wall are more sensitive to autolysis than collagen (8).…”
Section: Introductionmentioning
confidence: 99%
“…A ranking test was conducted by nine panelists (aged 21-23 years; all were female students of the Prefectural University of Hiroshima) [25,26]. The panel evaluated the pleasant steamed fish odor and the oily odor of cooked fish slices.…”
Section: Sensory Evaluationmentioning
confidence: 99%
“…The fermentation also gives specific and favorable aroma, taste, and color to the products. On the other hand, these marine products often contain a large amount of oxidatively unstable EPA and DHA (Giri and others , ; Funaki and others ). For the long life preservation, the oxidation of these PUFAs should be effectively protected.…”
Section: Introductionmentioning
confidence: 99%